2019
DOI: 10.33224/rrch/2019.64.7.04
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of AAm-co-alginate hydrogels swelling kinetics

Abstract: In this study, cross-linked acrylamide-co-alginat hydrogels were synthesized by free radical polymerization in aqueous solutions of acrylamide and of acrylamide with sodium alginate as comonomer. For each copolymerization, four different compositions were used and in all systems a concentration of a crosslinker such as oxalic acid and polyethylene glycol dimethacrylate (PEGDMA 500) was employed. As a result of swelling tests, the influence of crosslinkers and the relative content of sodium alginate on the swel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This result is also supported by the sol–gel analysis ( Table 2 ). Moreover, some studies have reported that an increase in the degree of swelling is correlated with low values of k 1,s [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result is also supported by the sol–gel analysis ( Table 2 ). Moreover, some studies have reported that an increase in the degree of swelling is correlated with low values of k 1,s [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the different drug delivery systems, oral controlled release (CR) formulation is the most preferred in the pharmaceutical industry. [1][2][3] Hydrogels are generally used in matrix tablets in light of their superior characteristics such as flexibility. 4 Oral controlled release systems are one of the most desirable methods due to their low cost and risk of dose dumping and easy manufacturing route.…”
Section: Introduction *mentioning
confidence: 99%